Some modal logics associated to the reasoning of intelligent agents (2008)
The hierarchies of systems SCR – nT4, SCR – nT5 and SCR – nD45 are presented with n> 3, in which the notion of belief is formalized in the sense of justified belief, knowledge and conviction respectively, resulting in systems of Doxástic and epistemic logics in which the problem of logical omniscience can be partially controlled. The systems are characterized with Kripke-style semantics, in which the length of the possible world chains is restricted depending on the type of reasoner. Thus, the depth of a model corresponds to the maximum length of the chains of possible worlds that appear in the model, resulting in the models of depth n being associated with the deductive systems SCR-nT4, SCR-nT5 and SCR-nD45.